2020
DOI: 10.1016/j.scitotenv.2019.134816
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of silver nanoparticles on Vicia faba: Evaluation of particle size effects on photosynthetic performance and leaf gas exchange

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Previous studies found that AgNP toxicity was influenced by particle size with smaller AgNPs (6 nm) inhibiting plant growth more than did identical concentrations of larger (25 nm) NPs (Yin et al, 2011). Similarly, Falco et al (2020) found that the adverse effects on the photosynthetic activity to Vicia faba by AgNPs was increasing with decreasing particle size (Falco et al, 2020). Moreover, particle size could also affect the adhesion of NPs on the wheat leaves, as the percentage of 3 nm AuNPs adhesion to leaves was almost twice than that of 10 nm (Avellan et al, 2019).…”
Section: Size Distributions Of Ag-containing Particles In Planta Following Foliar and Root Exposurementioning
confidence: 97%
“…Previous studies found that AgNP toxicity was influenced by particle size with smaller AgNPs (6 nm) inhibiting plant growth more than did identical concentrations of larger (25 nm) NPs (Yin et al, 2011). Similarly, Falco et al (2020) found that the adverse effects on the photosynthetic activity to Vicia faba by AgNPs was increasing with decreasing particle size (Falco et al, 2020). Moreover, particle size could also affect the adhesion of NPs on the wheat leaves, as the percentage of 3 nm AuNPs adhesion to leaves was almost twice than that of 10 nm (Avellan et al, 2019).…”
Section: Size Distributions Of Ag-containing Particles In Planta Following Foliar and Root Exposurementioning
confidence: 97%
“…The analysis of NPQ' i.e the last saturated light pulse, when the seeds were already adapted to darkness, shows that CuO NPs induced changes in this parameter at all concentrations, evaluated relative to the control, causing a significant increase at 48 and 72 h when cotyledons are being formed. In a study carried out with Vicia faba, it was showed that the NPQ' values increased in the leaves containing the Ag NPs, which demonstrates that NPs may cause an increase in the dissipation of light energy by nonphotochemical forms, instead of photochemical processes (Falco et al 2020). However, after 72 h, a reversal in the behaviour of the NPQ occurred, where a significant decrease after 120 h was observed; this may be due to the formation of the fi rst leaves and the transformation of the seed into seedling, being the plant able to performing self-adjustment.…”
Section: Fluorescence Kinetics Of Chlorophyll Amentioning
confidence: 99%
“…The most favorable and used AgNPs and their complex nanoparticle have been attributed to their diverse range in each class of pesticides due to low toxicity but still many reported published that explained the drawback of these smart nanoagrochemicals [ 61 , 140 , 141 ] (Table 4 ). For example, In Vicia faba , the AgNPs internalization in leaves can abrupt the stomatal conductance CO 2 assimilation rate and photosystem II [ 142 ]. Furthermore, the binding of AgNPs attaches with Chlorophyll forming a hybrid, that excites electrons 10 times due to fast electron–hole separation and plasmon resonance effect.…”
Section: Drawbacks Using Nanoagrochemicals On Plantsmentioning
confidence: 99%